2015
DOI: 10.1016/j.mtcomm.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

New aromatic polyamides and polyimides having an adamantane bulky group

Abstract: This paper reports the synthesis and characterization of a new rigid diamine monomer, having a spiro carbon moiety and an adamantane bulky group in its structure; namely spiro-(adamantane-2,9′(2',7'-diamino)-fluorene) (SADAF). After its synthesis, using a straightforward methodology, a novel family of aromatic polyimides (PIs) and polyamides (PAs) has been attained by reaction of SADAF with three aromatic dianhydrides and two diacid chlorides, respectively. Two of the polyimides were obtained through the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 47 publications
0
22
0
2
Order By: Relevance
“…Wykazują one doskonałą stabilność termiczną, dobre właściwości mechaniczne, zwiększoną odporność chemiczną i wysoką temperaturę zeszklenia. PlazaLozano [83] badał syntezę i właściwości nowych polimerów tego typu otrzymanych z monomerów, do których wprowadzono fluoren (tricykliczny węglowodór aromatyczny), spirany (pierścienie węglowodorowe połą-…”
Section: Polimery O Dużej Odporności Termicznejunclassified
“…Wykazują one doskonałą stabilność termiczną, dobre właściwości mechaniczne, zwiększoną odporność chemiczną i wysoką temperaturę zeszklenia. PlazaLozano [83] badał syntezę i właściwości nowych polimerów tego typu otrzymanych z monomerów, do których wprowadzono fluoren (tricykliczny węglowodór aromatyczny), spirany (pierścienie węglowodorowe połą-…”
Section: Polimery O Dużej Odporności Termicznejunclassified
“…Similar studies were with aromatic polyamides containing 1-adamantanemethoxy substituted triphenylamine and the obtained membranes to analyze gas separation processes. Plaza-Lozano et al [75] reported the synthesis of polyamides and polyimides with high T g values above 350 • C and onset degradation temperatures higher than 450 • C. Polymers were prepared from a rigid diamine monomer, namely spiro-(adamantane-2,9 (2 ,7 -diamino)-fluorene) (Scheme 15, P30). The values of permeability and selectivity showed well-balanced gas productivity, in particular for the CO 2 /CH 4 separation.…”
Section: Film Membranes and Transport Propertiesmentioning
confidence: 99%
“…In addition, alicyclic units are introduced into diamines as side groups to prepare some special polyimides. For example, Plaza‐Lozano et al synthesized a diamine 20 with an adamantane side group through the nitration and hydrogenation reduction with Pd/C as shown in Scheme …”
Section: Synthesis Of Polyimides With Various Side Groupsmentioning
confidence: 99%
“…Generally, the gas permeability of polyimide films can be increased by improving the fractional free volume (FFV). It is a good approach to increase the FFV of polyimides by introducing side groups into polyimide backbone, including phenyl, tert ‐butyl, and alicyclic units . However the gas permselectivity decrease with increasing FFV correspondingly; that is, the polyimide gas separation membranes still suffer from a trade‐off between gas permeability and permselectivity.…”
Section: The Effects Of Side Groups On Specific Properties Of Polyimidesmentioning
confidence: 99%